Cubic ZnP2 nanowire growth catalysed by bismuth. Issue 11 (4th March 2021) - Oh, Seung Hwan; Kim, Yong
Abstract : The ZnP2 nanowires catalysed by bismuth had a cubic γ-ZnP2 structure, which is known to be stable only at pressures higher than 1.5 GPa, and its existence is a matter of debate. Abstract : Zn3 P2 and ZnP2 nanowires were grown by physical vapour transport using a bismuth catalyst. Bismuth with a low surface energy and melting temperature is an ideal catalyst for the growth of Zn–P binary nanowires. The ZnP2 nanowires were synthesized using a Zn3 P2 source with extra phosphorus vapour supplied from a separate phosphorus source. The Zn3 P2 nanowires had a conventional α-Zn3 P2 tetragonal crystal structure. Surprisingly, the ZnP2 nanowires had a cubic γ-ZnP2 structure, which is known to be stable only at pressures higher than 1.5 GPa, and its existence is a matter of debate. We observed that Bi catalyst was the deterministic parameter for the formation of γ-ZnP2 . The lattice constants ( a = 0.53578 nm) of the nanowires were determined from their d -spacing. Unlike the α-Zn3 P2 nanowires, the γ-ZnP2 nanowires showed a Raman band (430–470 cm −1 ) because of the internal vibrations of infinite phosphorus chains. From the contact angle analysis, the growth of the γ-ZnP2 nanowires when catalysed by bismuth, was dominated by centre nucleation rather than triple phase boundary nucleation. A nucleus with smaller dimensions is energetically favorable for centre nucleation, and the γ-ZnP2 nucleus formed during the initial stage of nucleation resulted in the formation of the cubic γ-ZnP2 nanowires. The centre nucleation model may explain the stability of γ-ZnP2 phase even at the synthesis pressure (100–600 Torr).